(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Seda Hotel is undergoing an Online Hotel Booking System project to offer consumers throughout the world a quick and simple option to book hotels online. Web pages that may be accessed through a website browser make up the interface of the online hotel booking system. Users can access the system anytime, anywhere, and use it to book rooms at Seda Hotel. The Online Hotel Booking System is a user-friendly program. Following its easy and straightforward GUI (Graphical user interface) design, anyone who knows how to use a Web browser may quickly make a booking, update the booking details, cancel the booking, change the personal profile, examine the booking history, or view the hotel information. The results of this study reveal that the hotel is doing a great job in providing guest satisfaction to the customers. The respondents asked how effective online advertisements are in hotel accommodations and the challenges or issues encountered in online advertisements towards the hotel, booking as agreed. It was determined that customer contentment with the Environment, Service, and Amenities was highly noticed. Except for Reach and Presentation, where the survey indicated that customers had the lowest satisfaction level, the hotel is advised to maintain the quality of the operations that rated with the highest satisfaction and observation.